Skewness map: estimating object orientation for high speed 3D object retrieval system. (2018) - Sintunata, Vicky; Kaminishi, Kurumi; Aoki, Terumasa
3D object retrieval system is a system where a similar or the same object in the database should be retrieved given a 2D query image (sketches or photographs). Unfortunately, as the appearance of 3D object might vary depending on the viewing directions, a vast amount of 2D rendered images must be processed (matched) to solve this problem. In this paper, we present a novel method called skewness map to relieve this problem. Skewness map can estimate the orientation of the object and select a few representative images accurately from the database; therefore matching every image in the database can be avoided. Experimental results show the retrieval system becomes much faster (14 times faster in matching time) and accurate in estimating the object orientation (less than one-degree error in average).